Misinterpreted Myoepithelial Carcinoma of Salivary Gland: A Challenging and Potentially Significant Pitfall. (May 2019) - Xu, Bin; Mneimneh, Wadad; Torrence, Dianne E.; Higgins, Kevin; Klimstra, David; Ghossein, Ronald; Katabi, Nora
Abstract : Myoepithelial carcinoma (MECA) is an underrecognized challenging entity with a broad morphologic spectrum. Misinterpreting MECA is not uncommon as distinguishing it from its mimics, especially cellular myoepithelial-rich pleomorphic adenoma (PA), can be difficult. We described 21 histologically challenging cases of MECAs (16 MECA ex-PA and 5 MECA de novo). All MECAs ex-PA were intracapsular or minimally invasive except for 3 cases. Eighteen (86%) were initially misinterpreted as benign neoplasms, including PA (10), atypical PA (5), and myoepithelioma (3). The remaining 3 were initially diagnosed as malignant (MECA ex-PA) but were histologically challenging. Histologic features that were found most helpful in recognizing the malignant nature of MECA included: uniformly cellular myoepithelial proliferation with an expansile nodular lobulated pattern (all cases) and alternate hypocellular and hypercellular zonal distribution (76% of cases). Among the 16 MECA patients with follow-up, 14 (87.5%) progressed: 10 developed local recurrence and 5 distant metastases. In contrast, only one of 33 patients with cellular PA (control group) recurred locally. Ten of the 14 MECAs that progressed were MECA ex-PA, and 12 (85%) had an initial benign diagnosis. Two patients with MECA ex-PA died of their disease; one had an initial diagnosis of PA. MECA is a histologically challenging entity that closely mimics PA and seems to carry a significant risk of recurrence. Areas of clonal appearing cellular myoepithelial growth with an expansile nodular lobulated pattern and zonal cellular distribution distinguish the majority of MECAs and may serve as useful diagnostic histologic features to differentiate MECA from its benign mimics.